IMPACT AND VULNERABILITY OF DISTANCE LEARNING ON THE MENTAL HEALTH CONDITIONS OF STUDENTS - Raden Rachmad Aditya; Zuhrotun Ulya (Journal of Psychiatry Psychology and Behavioral Research, 2021)
AbstractBackground: Since the first cases of COVID-19 were discovered, various countries have sought various methods and ways to deal with the pandemic. Some adaptations also need to be made to avoid further adverse effects. One of the ways is by doing lock-down so that distance learning is implemented using various educational media. The face-to-face or offline learning system that has been applied as a learning method has also been changed to a distance or online method. This has the potential to have a negative impact on the mental health of students. This study aims to discuss the impact and vulnerability of students to distance or online learning methods.Method: Researchers used 15 journals and literature that discuss the impact and vulnerability of distance learning on students' mental health conditions. Â Conclusion: Distance or online learning is one of the methods to reduce the spread of covid, but this has a negative impact on mental health especially on the students. The effects experienced by students include anxiety, mild to severe stress, social media fatigue, and depression. The things that underlie this impact have several factors such as unfamiliarity and need for adaptation time, the ability to use technology, a heavy burden of responsibility, and concerns about the economic burden of parents to finance learning activities. In this pandemic condition, efforts from all parties are needed so that the bad impact on the mental health of students can be minimized.